The Comparison of Sex Education with and without Religious Thoughts in Sexual Function of Married Women - Sedigheh Yousefzadeh; Nahid Golmakani; Fatemeh Nameni (Mashhad University of Medical Sciences, 2017)
Background & aim: One of the most important events in human life is marriage. Sexual satisfaction is one of the effective factors in a successful marriage. Accordingly, sexual health education is necessary. Sex education should be in line with the cultural, religious, and social infrastructures of the society. The aim of this study was to compare the effect of sex education with and without religious teachings on sexual performance of married women. Methods: This clinical trial with a pretest-posttest design was performed in four health centers that were selected through multi-stage cluster sampling, in 2013. A total of 64 women were chosen with regard to the inclusion criteria, such as formal marriage and first marriage, age of marriage ≥ 1, married life with husband, monogamous marriage, and participating in training sessions (sexual health education and sexual health based on religious teachings) that were held for six weeks. Female Sexual Function Index (FSFI) and a demographic characteristics form were used to collect the data. Data analysis was performed using descriptive statistics, t-test, and Pearson's correlation coefficient in SPSS, version 16. Results: In the intervention group, the mean score of Female Sexual Function Index was significantly different before and after the training program (P=0.03). The subgroups of sexual desire, orgasm, and sexual satisfaction in the intervention group and subgroups of arousal and sexual satisfaction in the control group were significantly different after the intervention (P